Implementation of playful strategies to improve academic performance in mathematics among sixth-grade students at El Bosque School in the city of San José de Cúcuta. (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2013)
The following research project aims to contribute to the teaching and learning process in mathematics for sixth-grade students in class 6B at Gimnasio El Bosque School through the implementation of playful strategies that strengthen learning and contribute to the development of mathematical knowledge, taking into account that these students' academic performance is low.Therefore, the relevant contributions of this work are presented through exercises to be worked on in the form of playful games, providing students with immediate understanding in terms of interest, motivation, and comprehension of the skills involved in knowledge of: operations with natural numbers, equations, and metric measurements. Therefore, it was verified that through the implementation of these strategies, a more effective and meaningful performance of mathematical knowledge can be achieved than that normally developed under traditional techniques (using blackboards, texts, and exercises), which represent a greater degree of difficulty for students.